1991
DOI: 10.1002/ar.1092300412
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the cellular interaction between thymocytes and a thymic stromal cell line (TEL‐2)

Abstract: In a previous study (Nakashima et al., Eur. J. Immunol., 20: 47-53, 1990), a cloned stromal cell line TEL-2 was established from Balb/c mouse thymus. Incubation of thymocytes with TEL-2 cells resulted in the selective elimination of CD4 and CD8 double-positive thymocytes from the culture. In the present report, both phase-contrast and scanning electron microscopes were used to examine, at various time intervals, TEL-2 cells cocultivated with thymocytes in order to elucidate the kinetic sequence of their cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The nursing activity of the R-TNC.1 cell line was manifested by the engulfment (emperiopolesis) of thymocytes after their binding to TEC (Č olić et al, 1994). The characteristics of the line appear to be identical with TNC reported by Wekerle et al (1980), and mouse stromal cell lines which formed characteristics complex structures with thymocytes in the monolayers and hanging drop culture system (Itoh et al, 1988;Nishimura et al, 1990;Hiramine et al, 1990;Hirata et al, 1991;Li et al, 1992). To our knowledge this is the first line with nursing characteristics established from the rat thymus.…”
Section: Dynamics Of Thymocyte Emperiopolesis By the R-tnc1 Cell Linesupporting
confidence: 75%
See 1 more Smart Citation
“…The nursing activity of the R-TNC.1 cell line was manifested by the engulfment (emperiopolesis) of thymocytes after their binding to TEC (Č olić et al, 1994). The characteristics of the line appear to be identical with TNC reported by Wekerle et al (1980), and mouse stromal cell lines which formed characteristics complex structures with thymocytes in the monolayers and hanging drop culture system (Itoh et al, 1988;Nishimura et al, 1990;Hiramine et al, 1990;Hirata et al, 1991;Li et al, 1992). To our knowledge this is the first line with nursing characteristics established from the rat thymus.…”
Section: Dynamics Of Thymocyte Emperiopolesis By the R-tnc1 Cell Linesupporting
confidence: 75%
“…However, binding of TH cells was stronger in comparison to thymocytes. Hirata et al (1991) also found that the number of thymocytes adhering to the mouse TEL-2 line with nursing activity was greatest at 1 h, followed by their significant detachment after prolonged cocultivation. We have previously demonstrated that LFA-1 and its ligand ICAM-1 are partly involved in the binding of thymocytes to both cortical, R-TNC.1 and medullary (TE-R2.5) cell lines in the early adhesion phase (30 min) (Č olić et al, 1994; 1997).…”
Section: R-tnc1 Cell Line Binds Both Viable and Apoptotic Thymocytesmentioning
confidence: 74%
“…7d), followed the ingestion of thymocytes by TEL-2 cells. The ultrastructure of these binding sites may suggest the presence of specific receptors for cellular recognition between thymocytes and thymus stromal cells (TEL-2 cells) (LaRochelle and Jones, 1989;Hirata et al, 1991).…”
Section: Prominent Membrane Events Between the Phase Of Attachment Anmentioning
confidence: 99%
“…Thus, TEL-2 cells are considered to play a role in the disappearance of DP thymocytes. In a follow-up study with SEM and transmission electron microscopy (TEM), Hirata et al (1991) have shown that as an initial event for the process of the selective elimination of DP thymocytes from the culture, the attachment between the thymocyte and TEL-2 cell leads to a migration of thymocytes between the TEL-2 processes. Similar cellular interactions between thymocytes and thymic stromal elements have been described in vitro (LaRochelle and Jones, 1989).…”
mentioning
confidence: 99%